Branding Politik Caleg Perempuan dari Partai Islam: Studi Kasus Lilis Nurlia dan Eka Widyani Latief di Kota Bekasi - Wiji Setiyani (Universitas Warmadewa, 2022)
Elections of 2019 are simultaneous elections. Elections 2019 require candidates to do a number of things to win the elections. Political branding is the common way of legislature candidates. Lilis Nurlia and Eka Widyani Latief are candidates for legislative members in Bekasi City from the Prosperous Justice Party (PKS). Interestingly, Lilis Nurlia used a success team while Eka Widyani Latief did not use a successful team in facing the 2019 election. Lilis Nurlia does her political branding through face-to-face media and social media and carries the name of the party on every occasion. This study aims to look at the political branding of Lilis Nurlia and Eka Widyani Latief in facing the 2019 election in Bekasi City because there are still few studies that discuss political branding, especially in female legislative candidates. This research uses Kapferer political branding theory to analyze the experience of political branding implemented Lilis Nurlia and Eka Widyani Latief. This research uses qualitative research with a case study approach. The author obtained primary data from the results of semi structure in-depth interviews and secondary data from article documents, journals, document archives, and so on. The results of the study obtained that Lilis Nurlia and Eka Widyani Latief were legislative candidates with sequence number 1. Lilis Nurlia does political branding with various activities mainly through tabloids. Lilis Nurlia also uses a group approach to approach the community, while Eka Widyani Latief also carries out various activities, especially gatherings and social relations approached to approach society. Lilis Nurlia and Eka Widyani Latief also introduced themselves and shared the activity on social media.